Testimony of a Bosnian - Tanović-Miller, Naza, 1938- (Eastern European studies (College Station, Tex.), 2001)
"Surrounded by Terror and genocide, Naza Tanovic-Miller and her family witnessed starvation, rape, and murder during the horrible war in Bosnia and the tense days and nights that led up to it. Now Tanovic-Miller gives a personal, riveting account of these dreadful events, a testimony that tells more than the news accounts Americans watched at the time." "Seeking refuge in her husband's home country of the United States in October, 1992, Naza Tanovic-Miller and her husband, Harry Miller immediately began efforts to raise the awareness of Americans about the ethnic cleansing taking place in Bosnia. The couple conducted an intense letter-writing campaign to prominent politicians and officials and organized gatherings and lectures to expose the truth about the desperate situation, hoping that some commitment would be made in defending Bosnia. Their efforts fell largely on deaf ears, and they were sorely disappointed by the lack of response from prominent officials." "Tanovic-Miller unflinchingly identifies the actual perpetrators of the Bosnian crisis, and she also unapologetically calls to task those who had the power to prevent the worst of the atrocities but did not."--Jacket